Answer:
x = 2
y = 5
Step-by-step explanation:
3x + y = 11 equation (1)
-x + y = 3 multiply this equation by -1
x - y = -3 equation (2)
by adding 2 equations
4x = 8
x = 2
by sub. in Equation (2)
2 - y = -3
y = 2+3
y = 5
Answer: 24x^3 sqrt5x -4x^3 sqrt10x
Step-by-step explanation:
Show in the photo attached.
Answer:
a
Step-by-step explanation:
Answer:
2x+1
Step-by-step explanation:
x = 1st integer
x+1 = next consecutive integer
The sum is
x+ (x+1)
Combine like terms
2x+1
Answer:
Srry umm can you zoom in I cant see srry!
Step-by-step explanation: